Training in Ultrasound to Determine Gestational Age in Low- and Middle- Income Countries: A Systematic Review - Viner, Alexandra C.; Okolo, Isioma D.; Norman, Jane E.; Stock, Sarah J.; Reynolds, Rebecca M. (Frontiers in Global Women's Health, 2022)
ABSTRACT Introduction Establishing an accurate gestational age is essential for the optimum management of pregnancy, delivery and neonatal care, with improved estimates of gestational age considered a public health priority by the World Health Organisation (WHO). Although ultrasound is considered the most precise method to achieve this, it is unavailable to many women in low- and middle- income countries (LMICs), where the lack of trained practitioners is considered a major barrier. This systematic review explores what initiatives have previously been undertaken to train staff to date pregnancies using ultrasound, which were successful and what barriers and facilitators influenced training. Methods The systematic review was conducted according to PRISMA guidelines and the protocol registered (PROSPERO CRD42019154619). Searches were last performed in July 2021. Studies were screened independently by two assessors, with data extracted by one and verified by the other. Both reviewers graded the methodological quality using the Mixed Methods Assessment Tool. Results were collated within prespecified domains, generating a narrative synthesis. Results 25/1262 studies were eligible for inclusion, all of which were programme evaluations. 18 were undertaken in Africa, 3 in South-East Asia, 1 in South America and 3 across multiple sites, including those in Africa, Asia and South America. 5 programmes specified criteria to pass, and within these 96% of trainees did so. Trainee follow up was undertaken in 18 studies. 10 met recommendations for training outlined by the International Society of Ultrasound in Obstetrics and Gynaecology (ISUOG) but only 1 met the current standards set by the WHO. Discussion This systematic review is the first to evaluate this topic and has uncovered major inconsistencies in the delivery and reporting of basic obstetric ultrasound training in LMICs, with the majority of programmes not meeting minimum recommendations. By identifying these issues, we have highlighted key areas for improvement and made recommendations for reporting according to the RE-AIM framework. With an increasing focus on the importance of improving estimates of gestational age in LMICs, we believe these findings will be of significance to those seeking to develop and expand the provision of sustainable obstetric ultrasound in LMICs.